Modo de ação de Mo-D3, uma fração proteica hipoglicemiante de folhas de Moringa oleífera Lam., em camundongos C57BL/6 hiperglicêmicos - Cardozo, Claudia Johana Pérez (2023)
Diabetes mellitus is a worldwide health problem. In the search for alternatives to oral hypoglycemic agents conventionally used in the treatment of diabetes, molecules of natural origin derived from plants stand out. Moringa oleifera Lam., where it is widely used in traditional medicine. Several studies have demonstrated, among the many properties of moringa, a hypoglycemic activity. A hypoglycemic effect, was observed that a protein fraction obtained from moringa leaves in mice with alloxan-induced diabetes. Thus, the aim of this study was to optimize the production and evaluate the mode of action of the protein fraction from moringa leaves called Mo-D3. This fraction was obtained by precipitating the protein extract of the leaves with ammonium sulfate followed by chromatographic separation in a DEAE-cellulose matrix. For the in vivo experiments aimed at elucidating the mode of action, male C57BL/6 mice were used, with the following tests being performed: Glucose tolerance test, analysis of liver and muscle glycogen content; analysis of serum lipid profile, evaluation of intestinal disaccharidases activity, insulin tolerance test and evaluation of GLUT4 and insulin gene expression. Statistical analyzes were performed using the variance analysis test (ANOVA) followed by the multiple comparison test (Bonferroni test), based on the continuity of the variables under analysis. The results showed that Mo-D3 had a hypoglycemic effect in hyperglycemic mice. In addition, it decreased the total cholesterol value while increasing the HDL in serum, increased muscle and liver glycogen content, improved insulin resistance in animals treated with dexamethasone, and increased GLUT 4 and insulin expression. In conclusion, the Mo-D3 protein fraction has promising results that point to its potential use as an adjunct in the prevention and treatment of diabetes.